Tax Administration and Commercial Banks as Specific Factors of Informal Economy in Kosovo - KRASNIQI, Armand (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
In modern societies the definition of forms of informal economic activities has evolved dynamically. The definition used for this phenomenon by lawyers and economists includes transactions or economic operations not under control by state institutions, but not even interested to undertake actions to stop them. Thus, informality of more than 40% has become one of the most discussed issues in Kosovo politics. The passive way approached by government institutions in combating this negative phenomenon, is not only inadequate, but above all it has become a factor of high social risk. Tax Administration of Kosovo (TAK), together with banks as the second in range, have gradually become serious stimulus segments of informal activities. Even though state Tax Administration is aware that establishment of credit relations between banks and certain business entities is proceeded on the basis of documentation, which neither in the form nor in content is realistic, official or reliable, it does not consciously control it but tolerates it, and in the last phase of determining the profit tax it bases exactly on them.